Achieving One‐Step Surface Coating of Highly Hydrophilic Poly(Carboxybetaine Methacrylate) Polymers on Hydrophobic and Hydrophilic Surfaces. Issue 6 (27th May 2014) - Sundaram, Harihara S.; Han, Xia; Nowinski, Ann K.; Brault, Norman D.; Li, Yuting; Ella‐Menye, Jean‐Rene; Amoaka, Kagya A.; Cook, Keith E.; Marek, Patrick; Senecal, Kris; Jiang, Shaoyi
<x xml:space="preserve">Abstract</x> It is highly desirable to develop a universal nonfouling coating via a simple one‐step dip‐coating method. Developing such a universal coating method for a hydrophilic polymer onto a variety of surfaces with hydrophobic and hydrophilic properties is very challenging. This work demonstrates a versatile and simple method to attach zwitterionic poly(carboxybetaine methacrylate) (PCB), one of the most hydrophilic polymers, onto both hydrophobic and hydrophilic surfaces to render them nonfouling. This is achieved by the coating of a catechol chain end carboxybetaine methacrylate polymer (DOPA‐PCB) assisted by dopamine. The coating process was carried out in water. Water miscible solvents such as methanol and tetrahydrofuran (THF) are added to the coatings if surface wettability is an issue, as for certain hydrophobic surfaces. This versatile coating method was applied to several types of surfaces such as polypropylene (PP), polydimethyl siloxane (PDMS), Teflon, polystyrene (PS), polymethylmethacrylate (PMMA), polyvinyl chloride (PVC) and also on metal oxides such as silicon dioxide.